Pengaruh Kemampuan Karyawan dan Kedisiplinan Terhadap Kinerja Karyawan LPDDesa Adat Kepaon - Ida Ayu Trisna Wijayanthi; Tettie Setiyarti; Ni Kadek Winda Oktaviani (Forum Manajemen, 2023)
This study aims to determine the Effect of Employee Ability and Discipline on the Performance of LPD Employees in the Kepaon Traditional Village. This research is a quantitative study using the total sampling method or saturated sample because the number of employees is less than 100 employees so that the samples in this study are all 30 employees at the LPD in Kepaon Traditional Village. The data analysis technique in this study used the Multiple Regression technique with the SPSS method. The results of this study indicate that the Employee Capability variable and the Discipline variable have a significant partial effect on the Employee Performance variable at the Kepaon Traditional Village LPD. This is evidenced by the t-count value between the influence of employee abilities on employee performance at the Kepaon Traditional Village LPD and between the effect of work discipline on performance employees at the Kepaon Traditional Village LPD. Likewise the results of the calculation of the F test can be concluded that employee ability and discipline simultaneously have a significant relationship to employee performance at LPD Kepaon Traditional Village.